Academic Procrastination: How Does it Correlate with Students’ Self-Efficacy in Higher Education? - Pratama, Desta Nanda; Zulaikhah, Siti; Irawan, Rudy (Journal of Innovation and Research in Primary Education, 2025)
Academic procrastination remains a pervasive issue in higher education, negatively impacting both students' academic performance and psychological well-being. One key factor influencing procrastination is self-efficacy, defined as the belief in one’s ability to complete academic tasks. This study investigated the relationship between self-efficacy and academic procrastination among 120 students from the Islamic Education Department (PAI), 22nd cohort, enrolled in the Innovation in Learning course at UIN Raden Intan Lampung. Using a quantitative correlational design and total sampling, data were collected through two closed-ended questionnaires: a 25-item self-efficacy instrument (Cronbach’s α = 0.875) and a 20-item academic procrastination instrument (Cronbach’s α = 0.892). The data were analyzed using the Pearson Product Moment correlation test in SPSS version 26, after confirming normality via the Kolmogorov-Smirnov test. The results showed a significant negative correlation between self-efficacy and academic procrastination, indicating that students with higher self-efficacy are less likely to procrastinate, while those with lower self-efficacy tend to delay tasks more. Additionally, the coefficient of determination (R² = 0.312) revealed that 31.2% of the variance in academic procrastination can be explained by self-efficacy, with the remaining variance influenced by other factors such as motivation and time management. These findings highlight the importance of enhancing self-efficacy to reduce procrastination and improve academic outcomes. The study contributes to academic psychology literature and offers practical insights for educators to develop strategies that strengthen self-efficacy and reduce procrastination.